Perforator Flaps Covering Alloplastic Materials in Full-Thickness Chest Wall Defects Reconstruction: A Safe Option?. Issue 5 (May 2017) - Aubá, Cristina; Cabello, Álvaro; García-Tutor, Emilio; Vila, Antonio; Qiu, Shan Shan; Torre, Wenceslao
Abstract : Summary: Large full-thickness chest wall reconstruction requires an alloplastic material to ensure chest wall stability, as well as a flap that provides good soft-tissue coverage. The choice not to use perforator flaps over any mesh or inert material is often based on the concern that the vascularization would be inadequate. However, perforator flaps have shown good results in several reconstructive fields, minimizing donor-site morbidity and offering versatility when local tissues are unavailable or affected by radiotherapy. In this study, we present 4 cases of patients with full-thickness chest wall defects that were repaired with a double Marlex mesh, acrylic cement (n = 2) or a double patch of Goretex (n = 2) in combination with perforator flaps (3 deep inferior epigastric artery perforators and 1 lumbar artery perforator flap). The results we obtained are encouraging, and we believe the use of perforator flaps in combination with alloplastic materials should be considered as a reliable option for full-thickness chest wall defect reconstruction.